Co-production in healthcare: rhetoric and practice - Vennik, Femke D. (2016)
Co-production in healthcare is receiving increasing attention; however, insight into the process of co-production is scarce. This article explores why hospitals involve patients and staff in co-production activities and hospitals experiences with co-production in practice. A qualitative study with semi-structured interviews (N?=?27), observations (70 hours) and document analysis was conducted in five Dutch hospitals, which involved patients and staff in order to improve services. The results show that hospitals have different motives to involve patients and staff and have adapted existing methods to involve patients. Interestingly, areas of improvement proposed by patients were often already known. However, the process of co-production did contribute to quality improvement in other ways. The process of co-production stimulated hospitals thinking about how to realize quality improvements. Quality improvements were facilitated by this process as seeing patients and hearing their experiences created a sense of urgency among staff to act on the improvement issues raised. Moreover, the experiences served to legitimatize improvements to higher management bodies. - Reproduced.
Keywords: Health services